The Effect of Preventive Functional Exercises on Some Biomotor Abilities and Physiological Variables For Handball Players - Samer Mahdi Muhammad Saleh; Ahmed Yousif Miteb; Walead Ahmed Alrahahleh (Institute of Medico-legal Publications Pvt Ltd, 2021)
Handball is one of the games that has achieved great interest in recent years, it is one of the most importantpopular games in the world, when focusing on the nature of performance in handball, find that it needshigh energy to perform its skills with appropriate strength, speed And endurance, as it requires highlevelof biomotor abilities from players when performing its skills. The researchers noted the neglect ofthe preventive aspect of the players and the focus on aspects of achievement while prevention is no lessimportant than aspects of achievement, The aims of the research were preparing preventive functionalexercises, and identifying the effect of preventive functional exercises on some biomotor abilities andphysiological variables for handball players. Researchers used the experimental method to study theproblem of the research by implementation of the experimental design using pre-test and post-test. Theresearch’s community consisted of 20 players from the Karbala Sports Club, they were divided into twoequal groups (experimental and control groups). The researchers implemented pre-tests for players whorepresent the research community, Preventive exercises applied with members of the experimental groupfor 8 weeks, 3 session per week, 24 training sessions, Post-tests were conducted for the experimental andcontrol groups, After gathered data, it was processed statistically using the statistical package SPSS, Theresearchers concluded the preventive functional exercises have a positive effect on developing of somebiomotor abilities and physiological variables for handball players.